2020
DOI: 10.1111/head.13737
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1, Randomized, Open‐Label, Safety, Tolerability, and Comparative Bioavailability Study of Intranasal Dihydroergotamine Powder (STS101), Intramuscular Dihydroergotamine Mesylate, and Intranasal DHE Mesylate Spray in Healthy Adult Subjects

Abstract: Objective To investigate and compare the safety and the pharmacokinetics of dihydroergotamine (DHE) after administration of intranasal DHE powder (STS101), intranasal DHE spray (Migranal®), and intramuscular (IM) DHE injection in healthy subjects. Methods This was a 2‐part, active‐controlled, 3‐period crossover study over 3 weeks, separated by 1‐week washout periods. In part 1, 3 ascending dosage strengths of STS101 (1.3, 2.6, and 5.2 mg) were administered to 15 healthy subjects with no history of migraine. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…A Phase 1, randomized, open-label, safety, tolerability, and comparative bioavailability study of STS101 demonstrated quick systemic absorption, attaining effective DHE plasma concentrations (>1000 pg/mL) within 10 min. Although the pharmacokinetics of STS101 demonstrated values that were 2.3-fold higher than those of MIGRANAL, it utilized a 6 mg dose that was 300% of the approved MIGRANAL 2 mg dose [89]. The results of topline data from the EMERGE trial, a Phase 3, multicenter, single-dose, randomized, double-blind, placebo-controlled, parallel-group efficacy study, showed that although numerical differences were in favor of STS101, the study did not demonstrate statistically significant differences between dosage strengths (4 and 6 mg) compared to placebo on coprimary endpoints of pain and most bothersome symptom freedom (among photophobia, phonophobia, or nausea) at 2 h post-administration [90].…”
Section: Sts101mentioning
confidence: 99%
“…A Phase 1, randomized, open-label, safety, tolerability, and comparative bioavailability study of STS101 demonstrated quick systemic absorption, attaining effective DHE plasma concentrations (>1000 pg/mL) within 10 min. Although the pharmacokinetics of STS101 demonstrated values that were 2.3-fold higher than those of MIGRANAL, it utilized a 6 mg dose that was 300% of the approved MIGRANAL 2 mg dose [89]. The results of topline data from the EMERGE trial, a Phase 3, multicenter, single-dose, randomized, double-blind, placebo-controlled, parallel-group efficacy study, showed that although numerical differences were in favor of STS101, the study did not demonstrate statistically significant differences between dosage strengths (4 and 6 mg) compared to placebo on coprimary endpoints of pain and most bothersome symptom freedom (among photophobia, phonophobia, or nausea) at 2 h post-administration [90].…”
Section: Sts101mentioning
confidence: 99%
“…Another formulation of DHE utilizes a dry powder for administration, STS 101. It demonstrated excellent pharmacokinetics ( 88 , 89 ). STS101 achieved rapid and sustained high drug exposure with low variability.…”
Section: Dihydroergotamine Nasal Preparationsmentioning
confidence: 99%
“…( 101 ) Although not marketed, data from the clinical development program of MAP0004 is frequently used as reference for all DHE mesylate development products. ( 9 , 103 ) Migraine pain relief was reported as early as 10 minutes in some patients with severe pain (with significance at 30 minutes overall compared with placebo) in a Phase 3, placebo-controlled study of MAP0004. ( 95 ) In STOP 101, INP104 delivery resulted in high plasma exposure to DHE in the first 2 hours, with values similar to MAP0004 (1603 and 1447 h*pg/mL reported for INP104 and MAP0004, respectively), and in STOP 301 pain relief as an exploratory efficacy outcome was reported with INP104 as early as 15 minutes, the first timepoint investigated.…”
Section: Inp104 Clinical Data In Support Of Pod Technologymentioning
confidence: 99%